2010
DOI: 10.1111/j.1398-9995.2010.02432.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of the basophil activation test in deciding when to reintroduce cow’s milk in allergic children

Abstract: The BAT could be a valuable tool in the management of paediatric CMA in addition to specific IgE quantification and SPT, by contributing in determining whether an oral challenge can safely be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 40 publications
4
80
3
4
Order By: Relevance
“…BAT should be carried out as soon as possible after blood withdrawal [9,11,123], and its performance may depend on several factors, such as the type of vial used for specimen collection [109]. BATs have proved to be useful tools to diagnose early onset of allergy and anaphylactic adverse reactions, such as with drugs [124], but also in monitoring immunotherapy [125,126,127] and to reintroduce food to allergic children [128]. Multicenter and pilot studies have also been carried out in order to achieve a consensus agreement and to outline possible guidelines for BAT optimization and application [129,130,131].…”
Section: Resultsmentioning
confidence: 99%
“…BAT should be carried out as soon as possible after blood withdrawal [9,11,123], and its performance may depend on several factors, such as the type of vial used for specimen collection [109]. BATs have proved to be useful tools to diagnose early onset of allergy and anaphylactic adverse reactions, such as with drugs [124], but also in monitoring immunotherapy [125,126,127] and to reintroduce food to allergic children [128]. Multicenter and pilot studies have also been carried out in order to achieve a consensus agreement and to outline possible guidelines for BAT optimization and application [129,130,131].…”
Section: Resultsmentioning
confidence: 99%
“…This varied response has been described previously [22,23,24]. The consequence of this is that an oral challenge has to be performed on individuals who are low responders or nonresponders in the CD-sens test [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing CD-sens and skin prick test titration [20], nasal allergen challenge [20] and food challenges also indicated a good agreement [22]. Basophil activation tests measuring cell reactivity have also been evaluated in milk, egg and wheat allergy [23,24,25,] and, recently, Chinuki et al [16] showed that basophil reactivity could be useful in differentiating between subtypes of WDEIA caused by wheat and/or by HWP.…”
Section: Introductionmentioning
confidence: 99%
“…The basophil activation test (BAT) has recently also been described as the best method to assess clinical tolerance to peanuts (84). Good sensitivity and specificity have also been described for milk (85,86) and egg allergy (87). However, its usefulness to delineate whether patients can consume baked egg or milk is less clear (85,86).…”
Section: Oral and Sublingual Immunotherapy In Food Allergymentioning
confidence: 99%
“…Good sensitivity and specificity have also been described for milk (85,86) and egg allergy (87). However, its usefulness to delineate whether patients can consume baked egg or milk is less clear (85,86). In the context of OIT, reduced basophil activation corresponds to desensitization in OIT with peanut (80,88,89), egg (1,90), and milk (91).…”
Section: Oral and Sublingual Immunotherapy In Food Allergymentioning
confidence: 99%